CAMISETA ESCOLAR:AVALIAÇÃO DA CONFORMIDADE NA REDE PÚBLICA DE ENSINO - Santos, Vanderlei Oliveira dos (2006)
This dissertation is related with the control of quality and requirements for the supply of the shirts to be used as uniform by the students of the Brazilian State School System; the main important properties of the fibre and textile as well the recommendations for the proper manufacturing of those shirts were highlighted. This dissertation shows clearly the need of a technical specifications, informing the minimum requirements to be complied by manufacturer in order to guarantee the higher durability and better appeareance for the referred shirts to be bought by the Brazilian Government, esides that, it also informs how the shirts shall be furnished and all the acceptable tolerances. Some recommendations were presented in this work, in order to stabilish the quality requirements for the uniform shirts supply. Those recommendations also works as a guideline for the correct analysis of the shirts samples received by the laboratories accreditated by the National Institute of Metrology, Standardization and Industrial Quality - Inmetro during the technical evaluation stage during a public bid process.